Desempenho logístico do Brasil no mercado internacional: análise do índice LPI - Bazani, Camila (2017)
The facilitation of foreign trade is still a challenge for Brazil. In this scenario, researches confirm the relevance of logistics sector improvement in order to attract investments and reduce costs, helping to maintain a country global and economically competitive. Thus, it is fundamental to assess constantly a country's logistics performance to propose measures and reforms in order to gain competitive advantage in global market. The present study aimed to evaluate the logistics performance of Brazil in the international market based on the Logistic Performance Index (LPI) presented by the World Bank. It also aimed to diagnose the main areas that show symptoms of inefficiency logistics, highlighting differential aspects and proposing alternatives to be implemented that contribute to new investments in logistics operations of the international market. The proposed objectives were analyzed in light of the strategic positioning theory and the “Porter Diamond” model, considering that logistics efficiency is a strategic component and that competitive advantage of industries is transferred to the nation when they internationalize. More than that, LPI indicators are considered indicative of competitiveness among countries. It is a descriptive research with a quantitative approach, which used the following statistical methods for data analysis: regression analysis, cluster analysis, multiple comparison of means and Pearson's correlation coefficient. The necessary elements to develop this research were obtained through a documentary research with an analysis of World Bank reports and secondary data, having as basic source the information already collected and disclosed by the World Bank, in addition to data from AliceWeb and UNComtrade systems. We concluded that Brazil is a country with a medium logistics performance, although it is still far behind most of its main competitors. Its worst logistics performance consists of the customs dimension, while its best performance refers to timeliness. We also verified that developed countries are mostly grouped in the cluster with high logistics performance. Finally, there was a positive association between logistics performance and export volume, while there is a negative association between logistics performance and costs to import and export. It confirms the relevance of the logistics sector to trade flows and, consequently, to economic development.